Demographic, environmental and physiological predictors of gastrointestinal parasites in urban raccoons - Liana F. Wait; Shylo R. Johnson; Kathleen M. Nelson; Richard B. Chipman; Frederick E. Pogmore; Andrew P. Dobson; Andrea L. Graham (International Journal for Parasitology: Parasites and Wildlife, 2023)
Raccoons are host to diverse gastrointestinal parasites, but little is known about the ecology of these parasites in terms of their interactions with each other during coinfections, their interactions with host physiology and environmental factors, and their impact on raccoon health and survival. As a first step, we investigated the patterns of parasite infection and their demographic distribution in an urban-suburban population of raccoons trapped in the summers and autumns of 2018 and 2019. We collected faecal samples, demographic data, morphometric measurements, and blood smears, and used GPS data to classify trapping location by land cover type. Faecal floats were performed to detect and quantify gastrointestinal nematode eggs and coccidia oocysts, and white blood cell differentials were performed on blood smears to characterise white blood cell distributions. Data were analysed cross-sectionally and, where possible, longitudinally, using generalised linear models. Overall, 62.6% of sampled raccoons were infected with gastrointestinal nematodes, and 82.2% were infected with gastrointestinal coccidia. We analysed predictors of infection status and faecal egg count for three different morphotypes of nematode—Baylisascaris, strongyle, and capillariid nematodes—and found that infection status and egg count varied with Year, Month, Age class, Land cover, and coinfection status, though the significance of these predictors varied between nematode types. Gastrointestinal coccidia prevalence varied with Year, Month, Age class, strongyle infection status, and capillariid infection status. Coccidia oocyst counts were lower in adults and in October, but higher in females and in raccoons trapped in areas with natural land cover; furthermore, coccidia oocysts were positively associated with capillariid faecal egg counts. We found no evidence that gastrointestinal parasites influenced raccoon body condition or overwinter mortality, and so conclude that raccoons, though harbouring diverse and abundant gastrointestinal parasites, may be relatively tolerant of these parasites.